Lens development and disorders - molecular biology and genetics - Gillespie, Rachel (Henry Stewart Talks, 2016)
Overview of lens anatomy and function, Lens macrostructure/microanatomy and lens transparency, Molecular mechanisms of the vertebrate lens development, Factors contributing to normal lens physiology, The role of proteins integral to lenticular transparency, Genetics of lens abnormalities, The importance of precision diagnoses in congenital lens abnormality cases, Next generation sequencing technologies in the diagnosis of lens abnormalities